REpeated AutoLogous Infusions of STem cells In Cirrhosis (REALISTIC): a multicentre, phase II, open-label, randomised controlled trial of repeated autologous infusions of granulocyte colony-stimulating factor (GCSF) mobilised CD133+ bone marrow stem cells in patients with cirrhosis. A study protocol for a randomised controlled trial. Issue 3 (20th March 2015) - King, A; Barton, D; Beard, H A; Than, N; Moore, J; Corbett, C; Thomas, J; Guo, K; Guha, I; Hollyman, D; Stocken, D; Yap, C; et al.
Abstract : Introduction: Liver disease mortality and morbidity are rapidly rising and liver transplantation is limited by organ availability. Small scale human studies have shown that stem cell therapy is safe and feasible and has suggested clinical benefit. No published studies have yet examined the effect of stem cell therapy in a randomised controlled trial and evaluated the effect of repeated therapy. Methods and analysis: Patients with liver cirrhosis will be randomised to one of three trial groups: group 1: Control group, Standard conservative management; group 2 treatment: granulocyte colony-stimulating factor (G-CSF; lenograstim) 15 µg/kg body weight daily on days 1–5; group 3 treatment: G-CSF 15 µg/kg body weight daily on days 1–5 followed by leukapheresis, isolation and aliquoting of CD133+ cells. Patients will receive an infusion of freshly isolated CD133+ cells immediately and frozen doses at days 30 and 60 via peripheral vein (0.2×10 6 cells/kg for each of the three doses). Primary objective is to demonstrate an improvement in the severity of liver disease over 3 months using either G-CSF alone or G-CSF followed by repeated infusions of haematopoietic stem cells compared with standard conservative management. The trial is powered to answer two hypotheses of each treatment compared to control but not powered to detect smaller expected differences between the two treatment groups. As such, the overall α=0.05 for the trial is split equally between the two hypotheses. Conventionally, to detect a relevant standardised effect size of 0.8 point reduction in Model for End-stage Liver Disease score using two-sided α=0.05(overall α=0.1 split equally between the two hypotheses) and 80% power requires 27 participants to be randomised per group (81 participants in total). Ethics and dissemination: The trial is registered at Current Controlled Trials on 18 November 2009 (ISRCTN number 91288089, EuDRACT number 2009-010335-41). The findings of this trial will be disseminated to patients and through peer-reviewed publications and international presentations.